Developmental Coordination Disorder in School-Age Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The prevalence of developmental coordination disorder (DCD) in children, at 7 years of age, in a large UK birth cohort was determined using DSM-IV criteria, in a study at the University of Bristol, UK; and Utrecht University, Netherlands.